Are Amniotic Fluid Products Stem Cell Therapies? A Study of Amniotic Fluid Preparations for Mesenchymal Stem Cells With Bone Marrow Comparison. Issue 5 (April 2019) - Panero, Alberto J.; Hirahara, Alan M.; Andersen, Wyatt J.; Rothenberg, Joshua; Fierro, Fernando
Background: In vivo amniotic fluid is known to contain a population of mesenchymal stem cells (MSCs) and growth factors and has been shown to assist in healing when used as an adjunct in procedures across multiple medical specialties. It is unclear whether amniotic fluid products (AFPs) contain MSCs and, if so, whether the cells remain viable after processing. Purpose: To determine whether MSCs, growth factors, and hyaluronan are present in commercially available AFPs. Study Design: Descriptive laboratory study. Methods: Seven commercial companies that provide amniotic fluid were invited to participate in the study; 3 companies (the manufacturers of PalinGen, FloGraft, and Genesis AFPs) agreed to participate and donated AFPs for analysis. The AFPs were evaluated for the presence of MSCs, various growth factors relevant to orthopaedics (platelet-derived growth factor ββ, vascular endothelial growth factor, interleukin 8, bone morphogenetic protein 2, transforming growth factor β1 ), and hyaluronan by enzyme-linked immunosorbent assay and culture of fibroblast colony-forming units. These products were compared with unprocessed amniotic fluid and 2 separate samples of MSCs derived from human bone marrow aspirates. All groups used the same culture medium and expansion techniques. Identical testing and analysis procedures were used for all samples. Results: MSCs could not be identified in the commercial AFPs or the unprocessed amniotic fluid. MSCs could be cultured from the bone marrow aspirates. Nucleated cells were found in 2 products (PalinGen and FloGraft), but most of these cells were dead. The few living cells did not exhibit established characteristics of MSCs. Growth factors and hyaluronan were present in all groups at varying levels. Conclusion: The AFPs studied should not be considered "stem cell" therapies, and researchers should use caution when evaluating commercial claims that products contain stem cells. Given their growth factor content, however, AFPs may still represent a promising tool for orthopaedic treatment. Clinical Relevance: Amniotic fluid has been proposed as an allogenic means for introducing MSCs. This study was unable to confirm that commercial AFPs contain MSCs.